Molecular Characterization of Group A Human Rotavirus among Hospitalized Children and Adults in Bangladesh: Finding of Emerging G12 Strain (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):16-26.The abstract of this article is available on the PubMed website